2009
DOI: 10.1124/dmd.109.026674
|View full text |Cite
|
Sign up to set email alerts
|

Unbound Brain Concentration Determines Receptor Occupancy: A Correlation of Drug Concentration and Brain Serotonin and Dopamine Reuptake Transporter Occupancy for Eighteen Compounds in Rats

Abstract: ABSTRACT:It is a commonly accepted hypothesis that central nervous system (CNS) activity is determined by the unbound brain drug concentration. However, limited experimental data are available in the literature to support this hypothesis. The objective of this study was to test this hypothesis by examining the relationship between in vitro binding affinity (K I ) and in vivo activity quantified as the drug concentration occupying 50% of the transporters (OC 50 ) for 18 serotonin (SERT) and dopamine transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 29 publications
3
42
0
Order By: Relevance
“…It is widely held that drug activity in the CNS is caused by the unbound brain concentration, because it is that concentration that determines the drug's occupation of the receptors. This widely accepted concept was confirmed by Liu et al (2009) who showed that this unbound (biophase) concentration is approximately 1/100 of the total brain concentration for a number of agents, e.g., serotonin and dopamine transporter inhibitors (substances with molecular weights similar to tapentadol). Based on this, by using the brain concentration data (ng/g) for tapentadol (see Fig.…”
Section: Theorymentioning
confidence: 62%
“…It is widely held that drug activity in the CNS is caused by the unbound brain concentration, because it is that concentration that determines the drug's occupation of the receptors. This widely accepted concept was confirmed by Liu et al (2009) who showed that this unbound (biophase) concentration is approximately 1/100 of the total brain concentration for a number of agents, e.g., serotonin and dopamine transporter inhibitors (substances with molecular weights similar to tapentadol). Based on this, by using the brain concentration data (ng/g) for tapentadol (see Fig.…”
Section: Theorymentioning
confidence: 62%
“…Multiple reports (Kalvass et al, 2007;Liu et al, 2009b;Watson et al, 2009;Shaffer, 2010) have demonstrated for CNS transmembrane proteins, whose drug-binding site interactions in vivo are dictated by C ISF , the importance of unbound brain compound concentrations (C b,u ), another C ISF proxy, to project accurately receptor occupancy in rodents. In addition, it has been discussed how single-dose rat neuropharmacokinetics studies, which define temporal CNS intercompartmental concentration relationships via unbound brain, CSF, and unbound plasma area under the compound concentration-time curve (AUC) ratios, are useful to relate a molecule's different realms of CNS penetration and unbound concentration(s) to a specific in vitro or in vivo target-mediated effect (Shaffer, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This approach relies on an understanding of the relationship between drug concentrations in the plasma and CNS biophase that result in specific levels of target occupancy. The majority of studies that examine this relationship rely on single time-point determinations of target occupancy after a single-dose administration of the test agent (Hughes et al, 2005;Liu et al, 2009). Such single time-point determinations may misrepresent the true relationship between plasma drug concentration and CNS target occupancy at steady state, especially in cases in which the distribution of the drug from the plasma to the brain is relatively slow or the binding kinetics of the drug at the transporter (or receptor) are slow.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of SERT occupancy in humans and animals have historically adopted in vivo (humans and animals) or ex vivo (animals) radio-ligand binding methods by using well characterized radioligands such as [ 3 H/ 11 C] (3-amino-4-[2-[(di(methyl) 3,5,6,10b-hexahydropyrrolo[2,1-a]isoquinoline) (Huang et al, 2002;Hughes et al, 2005;Liu et al, 2009). By contrast, there are fewer ligands suitable for monitoring in vivo occupancy at NET in humans; however, the identification and characterization of such radioligands is ongoing (Logan et al, 2007;Ding et al, 2010;Hannestad et al, 2010;Gallezot et al, 2011).…”
Section: Introductionmentioning
confidence: 99%